MODERASI BERAGAMA SEBAGAI POLITIK HUKUM ISLAM DI INDONESIA: KAJIAN FILOSOFIS DAN YURIDIS TERHADAP PROGRAM PEMERINTAH - Bukhari Bukhari; Anwar Anwar; Azwir Azwir (Prodi Hukum Tata Negara Islam (Siyasah Syar'iyyah) STAIN Teungku Dirundeng Meulaboh, 2025)
This article explores religious moderation as a form of Islamic legal politics in Indonesia from both philosophical and juridical perspectives. Using a qualitative normative approach, the study analyzes how the concept of maqāṣid al-syarī‘ah (the higher objectives of Islamic law) and siyāsah syar‘iyyah (Islamic public policy) are reflected in the government’s policy on religious moderation initiated by the Ministry of Religious Affairs since 2019. The research argues that religious moderation represents not only a sociocultural strategy but also a legal-political manifestation of Islamic values aimed at ensuring justice, balance, and public welfare within Indonesia’s pluralistic society. Through an interpretative analysis of relevant literature, laws, and state policies, this study finds that the principle of moderation aligns harmoniously with the Pancasila-based constitutional framework and strengthens the position of Islamic law as an ethical foundation for national legal development. In conclusion, religious moderation serves as an adaptive expression of maqāṣid al-syarī‘ah in Indonesia’s democratic context, promoting peaceful coexistence, legal pluralism, and the realization of collective welfare (maslahah ‘ammah) as envisioned in Islamic jurisprudence.